STRATEGI PENGEMBANGAN USAHA JENANG PASCA PANDEMI MENGGUNAKAN METODE SWOT DAN QSPM PADA CV. MUBAROKFOOD CIPTA DELICIA - Nasya, Vilda Innaka; Arbainah, Siti; Ardian Widiarto (Pusat Penelitian dan Pengabdian bagi Masyarakat Politeknik Negeri Tanah Laut, 2024)
This research is applied research with a qualitative descriptive case study approach that aims to formulate a business development strategy after the Covid-19 pandemic at CV. Mubarokfood Cipta Delicia. Data was collected using observation, interview, documentation, and questionnaire methods. Data analysis was carried out using the IFE, EFE, CPM, IE, SWOT, and QSPM matrices. The result of the total IFE weighted score is 2.789 and the total EFE weighted score is 3.358. The total score based on CPM of 3,413 shows that the company is in the most superior position. The results of the IE Matrix analysis are in quadrant II (grow and build) by producing integration strategies and intensive strategies, which are further processed using the SWOT matrix and create eight alternative strategies. The strategy that best suits the condition of the company based on QSPM is to maintain quality and increase product innovation through cooperation with suppliers to achieve customer satisfaction with a TAS value of 6.691.